Tailored, iterative, printed dietary feedback is as effective as group education in improving dietary behaviours: results from a randomised control trial in middle-aged adults with cardiovascular risk factors - Wright, Janine; Sherriff, Jillian; Dhaliwal, Satvinder; Mamo, John (BioMed Central, 2011)
Background: Tailored nutrition interventions have been shown to be more effective than non-tailored materials inchanging dietary behaviours, particularly fat intake and fruit and vegetable intake. But further research examiningefficacy of tailored nutrition education in comparison to other nutrition education methods and across a widerrange of dietary behaviours is needed. The Stages to Healthy Eating Patterns Study (STEPs) was an interventionstudy, in middle-aged adults with cardiovascular risk factors, to examine the effectiveness of printed, tailored,iterative dietary feedback delivered by mail in improving short-term dietary behaviour in the areas of saturated fat, fruit, vegetable and grain and cereal intake.Methods: STEPs was a 3-month randomised controlled trial with a pre and post-test design. There were three experimental conditions: 1) tailored, iterative, printed dietary feedback (TF) with three instalments mail-delivered over a 3-month period that were re-tailored to most recent assessment of dietary intake, intention to change and assessment of self-adequacy of dietary intake. Tailoring for dietary intake was performed on data from a validated 63-item combination FFQ designed for the purpose 2) small group nutrition education sessions (GE): consisting of two 90-minute dietitian-led small group nutrition education sessions and 3) and a wait-listed control (C) group who completed the dietary measures and socio-demographic questionnaires at baseline and 3-months later. Dietary outcome measures in the areas of saturated fat intake (g), and the intake of fruit (serves), vegetables (serves), grain and cereals as total and wholegrain (serves) were collected using 7-day estimated dietary records. Descriptive statistics, paired t-tests and general linear models adjusted for baseline dietary intake, age and gender were used to examine the effectiveness of different nutrition interventions.Results: The TF group reported a significantly greater increase in fruit intake (0.3 serves/d P = 0.031) in comparison to GE and the C group. All three intervention groups showed a reduction in total saturated fat intake. GE also had a within-group increase in mean vegetable intake after 3 months, but this increase was not different from changes in the other groups. Conclusions: In this study, printed, tailored, iterative dietary feedback was more effective than small group nutrition education in improving the short-term fruit intake behaviour, and as effective in improving saturated fat intake of middle-aged adults with cardiovascular risk factors. This showed that a low-level dietary intervention could achieve modest dietary behaviour changes that are of public health significance.